Effect of hypertension on clinical outcomes in ischemic colitis - Huahui Zhang; Zijia Ma; Xianfeng Qiu; Shuangliang Gu; Jin Huang; Xuyang Liang; Zhimei Zhang (Annals of Medicine)
Background The aim of this retrospective study was to uncover the effect of hypertension on ischemic colitis (IC).Methods Patients with IC were divided into two groups—hypertension (HP) and nonhypertension (NHP) groups—on the basis of their history of hypertension. Clinical features, biochemical indicators, endoscopic findings, abdominal pain relief time (APRT), hospital stay, operation rate, incidence of gangrenous IC, and 30-day mortality of IC were evaluated. Factors associated with ulcers and severe pain were assessed by multivariable logistic regression analysis.Results A total of 213 patients were enrolled in this retrospective study. The mean age in the HP group was significantly higher than in the NHP group (mean, 68.4 years vs 60.9 years; p = 0.000), while no statistically significant difference in gender distribution was observed between the two groups (% female: 59.3% vs 66.4%; p = 0.507). Patients in the HP group were more likely to suffer from moderate (52.7% VS 37.7%; p = 0.036) and severe (22.0% vs 9.8%; p = 0.019) abdominal pain than those in the NHP group. The incidence of ulceration was significantly greater in the HP group than in the NHP group (22.0% vs 10.7%; p = 0.034). APRT (mean, 2.8 days vs 2.7 days; p = 0.585), hospital stay (mean, 6.5 days vs 6.2 days; p = 0.276), operation rate (3.3% vs 1.6%; p = 0.739), incidence of gangrenous IC (5.5% vs 2.5%; p = 0.430), and 30-day mortality (2.2% vs 0.8%; p = 0.797) of IC were not significantly different between the two groups.Conclusions Hypertension worsens clinical symptoms and endoscopic findings of IC but does not affect clinical outcomes.